Administrative performance and its relationship with the cognitive style (rigidity - flexibility) for management body members of the sport clubs - METEAB MUNAF, SUHAIR; Abdulateef Ali, Ali (International Journal of Psychosocial Rehabilitation, 2020)
Sports clubs and their administrative bodies are among the most important factors in the success of sports work and the achievement of achievements, but beyond that, in the field of participation in tournaments and their organization, as well as preparing high-level players according to age groups, as well as managing delegations participating in foreign tournaments and also working in all of this, it requires effective and successful bodies in order to do what it has in the right way that serves the game that these bodies represent. Psychology and sports management have a great role in creating an administration with special characteristics that qualify them to work under various circumstances and in various fields. Therefore, clubs and sports institutions have tended to develop the administrative aspects of all workers equally, and the interest of these clubs and institutions has increased in developing their administrative work through research and investigation in various aspects, including the psychological and administrative aspects. And through the researcher's follow-up of the activities of the clubs and the levels of their teams, as well as consulting with experts in this field, I found that it is better to study other variables for them that come on the administrative side, and perhaps the most important of them is the psychological aspect. Therefore, the importance of research came to find relationships between cognitive methods and administrative performance to identify the ability of members of the administrative bodies of sports clubs in managing the affairs of their teams in an optimal manner and evaluating their administrative performance.